2001
DOI: 10.1248/cpb.49.468
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Reactions. XXXIV.<SUP>1)</SUP> Enantioselective Deprotonation of Prochiral 4-Substituted Cyclohexanones Using Chiral Bidentate Lithium Amides Having a Bulky Group Instead of a Phenyl Group on the Chiral Carbon

Abstract: Lithium dialkylamides such as lithium diisopropylamide (LDA) are widely used in organic synthesis as strong bases with low nucleophilicity.2) We have previously reported enantioselective deprotonation 3) of prochiral 4-substituted cyclohexanones (1) using chiral lithium amides in the presence of excess trimethylsilyl chloride (TMSCl) (Corey's internal quench method 4) ) to isolate the corresponding lithium enolates (2) as trimethylsilyl enol ethers (3). 5) Among various chiral lithium amides examined, chiral b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Structural and solution-state investigations of chiral alkali metal amides have experienced a period of steady growth over the last 10 years largely due to their extensive use as chiral auxiliaries and reagents in asymmetric synthesis. In particular, chiral lithium amides play a prominent role in asymmetric deprotonation and addition reactions, allowing for the synthesis of biologically important molecules, such as β-amino acids and β-lactams, with high enantioselectivity. ,, Understanding the stereoselectivity of such reactions, and the structural chemistry of the reactive species or any intermediate complexes formed, allows more efficient and effective reagents to be designed.…”
Section: Introductionmentioning
confidence: 99%
“…Structural and solution-state investigations of chiral alkali metal amides have experienced a period of steady growth over the last 10 years largely due to their extensive use as chiral auxiliaries and reagents in asymmetric synthesis. In particular, chiral lithium amides play a prominent role in asymmetric deprotonation and addition reactions, allowing for the synthesis of biologically important molecules, such as β-amino acids and β-lactams, with high enantioselectivity. ,, Understanding the stereoselectivity of such reactions, and the structural chemistry of the reactive species or any intermediate complexes formed, allows more efficient and effective reagents to be designed.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Koga et al synthesized diamines with different N-alkyl groups and subsequently applied the corresponding lithium amides in the asymmetric deprotonation reactions. 12, 13 Henderson systematically studied magnesium amide base-mediated enantioselective deprotonation processes. 14,15 Despite the increasing use of polymeric chiral reagents in organic synthesis, the number of papers dealing with asymmetric deprotonation using polymer-supported CLAB's is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…This nonbiomimetic synthesis revealed that the double N-arylation is a powerful method for the construction of structurally complex carbazoles. The effective preparation of the hexa-heterocyclic structure in 1 by exploiting the intramolecular Friedel−Crafts-type Michael addition and Bachwald−Hartwig C−O coupling reactions would be applicable for the synthesis of natural products possessing complex multicyclic structures …”
mentioning
confidence: 99%